Somatic embryogenesis of the selected intergeneric hybrid between Phalaenopsis 2166 and Vanda ‘Saint Valentine’: Application of NAA and TDZ - Murni Dwiati; AGUS HERY SUSANTO; Iman Budisantoso (Smujo International, 2022)
Abstract. Dwiati M, Susanto AH, Budisantoso I. 2022. Somatic embryogenesis of the selected intergeneric hybrid between Phalaenopsis 2166 and Vanda' Saint Valentine': Application of NAA and TDZ. Nusantara Bioscience 14: 160-165. Intergeneric hybridization between Phalaenopsis 2166 and Vanda' Saint Valentine' has produced a hybrid seedling with several characters potentially developing into plant individuals with flowers of better performance. Therefore, identical clones of the selected hybrid should be developed into PLBs using an in-vitro culture technique employing somatic embryogenesis supported by the application of plant growth regulators. This study aims to unveil the effect of NAA and TDZ in stimulating the formation of identical clones of the selected intergeneric hybrid between Phalaenopsis 2166 and Vanda' Saint Valentine'. The experiment was arranged in a factorial Randomized Complete Block Design (RCBD) involving two factors, i.e., types of plant growth regulators and the levels of concentrations of each substance. It was found that the combination of NAA and TDZ significantly affected the growth of the identical clones. Furthermore, the combination of NAA 0.5 mgL-1 and TDZ 1.5 mgL-1 resulted in clones that potentially differentiate into PLBs. This finding indicates that NAA and TDZ should be applied appropriately to stimulate somatic embryogenesis in the intergeneric hybrid.